The combination of N-acetylcysteine and cyclosporin A reduces acetaminophen-induced hepatotoxicity in mice - Kaya Tektemur, Nalan; Erdem Guzel, Elif; Gul, Mehmet; Tektemur, Ahmet; Ozcan Yildirim, Sena; Kavak Balgetir, Merve; Enver Ozan, Ibrahim (Taylor & Francis Inc, 2021)
Acetaminophen (APAP)-induced hepatotoxicity is the most common cause of acute liver failure in worldwide. N-acetyl cysteine (NAC) is used as the APAP antidote. Cyclosporin A (CsA) is suppressed mitochondrial damage by binding cyclophilin, a mitochondrial pore transport component. The study aimed to evaluate the effects of NAC, CsA, and NAC+CsA treatments on APAP-induced hepatotoxicity in mice. Mice were randomly divided into five groups (n = 6). 400 mg/kg/ip/single dose APAP, 1200 mg/kg/i.p/single dose NAC and 50 mg/kg/i.p/single dose CsA were performed. Light and electron microscopic alterations were investigated in liver samples. Levels of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and liver glutathione (GSH) were analyzed. 3-nitrotyrosine and cytochrome c immunoreactivities were evaluated in liver tissue. Here, we found that APAP leads to histopathological and ultrastructural changes in mice liver. Also, APAP increased cytochrome c and 3-nitrotyrosine immunopositive staining. Besides, a significant decrease in liver GSH and an increase in serum AST and ALT levels were detected in the APAP group. Interestingly, NAC+CsA treatment improved histological alterations, cytochrome c, and 3-nitrotyrosine immunoreactivities and liver GSH, serum AST/ALT levels caused by APAP. We suggest that the combination of NAC and CsA reduces acetaminophen-induced hepatotoxicity in mice.
Keywords: N-acetylcysteine; cyclosporin A; acetaminophen; hepatotoxicity